Inclusive Education Management In Lazuardi Kamila Kindergarten Surakarta - Yuyun Dwi Prastyan; Darsinah Darsinah (Universitas Muhammadiyah Ponorogo, 2023)
This research aims to describe the management of inclusive education at Lazuardi Kamila Kindergarten Surakarta which includes planning, implementation and evaluation. This type of research is qualitative research with a case study research design. Data collection techniques through documentation, observation and interviews. The result of this research is that Lazuardi Kamila Kindergarten Surakarta has carried out planning, implementation and evaluation of inclusive education well. Planning is carried out at the beginning of the new school year by involving the foundation, principal, teachers, special teachers, parents, related parties and the community. In its implementation, children with special needs accompanied by a special teacher are in one class with children without special needs. In addition to using the official curriculum, a modified curriculum is also used. Evaluation is conducted on all school programmes and used for improvement in the following year.